Exploring the link: DNA methylation and kidney injury markers in farmers exposed to glyphosate-surfactant herbicides - Khacha-ananda, Supakit; Intayoung, Unchisa; Kohsuwan, Kanyapak; Wunnapuk, Klintean (Regulatory toxicology and pharmacology, 2025)
Glyphosate-surfactant herbicides (GSH), widely used herbicides, have raised concerns about their potential nephrotoxic effects. Despite extensive studies, the safety of GSH remains debatable. This study aimed to determine if occupational exposure to GSH causes detectable changes in renal injury biomarkers—specifically DNA methylation, KIM-1, TIMP2, and IGFBP7—in farmers regularly exposed to these chemicals. Two urine samples, pre-task (0-h) and post-task (24-h), were collected to analyze these biomarkers. No significant immediate changes were observed post-exposure, possibly due to personal protective equipment use. Moderate positive correlations were found between IGFBP7 and KIM-1, and IGFBP7 and TIMP2, suggesting early kidney injury. About 50% of subjects had a biomarker ratio greater than 1, indicating increased levels of IGFBP7, TIMP2, and KIM-1 after GSH exposure. This indicates that farmers who regularly spray GSH are at high risk of exposure, potentially leading to significant renal injury. Further long-term studies are needed to assess the chronic effects and validate these biomarkers for monitoring renal health in populations exposed to glyphosate. [Display omitted] •Moderate correlations between renal biomarkers suggest early kidney injury and cell death from occupational GSH exposure.•About 50% of subjects showed increased biomarker levels post-exposure, indicating potential early renal response to GSH.•Results highlight the need for long-term studies to assess chronic GSH effects and validate renal biomarkers for monitoring.